High-Isolation 3.5 GHz Eight-Antenna MIMO Array Using Balanced Open-Slot Antenna Element for 5G Smartphones - Li, Yixin; Sim, Chow-Yen-Desmond; Luo, Yong; Yang, Guangli (IEEE transactions on antennas and propagation, 2019)
A high-isolation eight-antenna multi-input multi-output (MIMO) array operating in the 3.5 GHz band (3.4-3.6 GHz) for future smartphones is proposed. Here, a novel balanced open-slot antenna is designed as an array antenna element, in which this antenna design can yield a balanced slot mode (with reduced ground effects) that can enhance the isolation between two adjacent input ports. Furthermore, by meticulously arranging the positions of the eight antenna elements, desirable polarization diversity can also be successfully achieved, which further mitigates the coupling between antenna elements. A prototype was manufactured to validate the simulation. A good impedance matching (return loss > 10 dB), high isolation (>17.5 dB), high total efficiency (>62%), and low envelope correlation coefficient (ECC, <0.05) were measured across the desired operation bandwidth. To verify the MIMO performance, ergodic channel capacity using the Kronecker channel model was calculated. The effects of hand phantom were also studied.